Medios de comunicación universitarios en Ecuador: Entrevistas con los directivos institucionales sobre el salto de la teoría a la práctica periodística (2019)
This study examines experiences using the Ecuadorian university media as training scenarios to allow students to gain experience in real spaces of journalistic practice, but within the educational sphere. For this purpose, a qualitative approach based on structured interviews with managers of twenty-four university media in this Latin American country was used. The responses were processed with the help of Atlas.ti software. The results highlight the high value of these learning scenarios when they constitute, in general terms, the first media space where future journalists are able to implement knowledge theoretically assimilated in the classroom. In addition, they are spaces in which students can participate actively, complement the activities of related subjects, and undergo pre-professional practical training on a voluntary basis. Despite this, certain divergences are found in relation to the complexity of learning by doing journalism and the students' academic achievement. Similarly, we identify some common routines in these spaces, such as the filtering of students' work or the trial and error method as the basis for reflection on journalistic practice. © 2019 Anàlisi.